A study of the perceptions of Year 4 pupils towards ten (10) most common ESL reading activities at SK Gersik, Kuching / Mohd Jelani Awg Abd Kadir - Awg Abd Kadir, Mohd Jelani (2006)
This project examines the perceptions of pupils towards ten most common ESL reading activities in their classroom. This study is conducted among Year 4 students of Sk. Gersik, Petra Jaya, Kuching. The whole populations of Year 4 students are involved in the study. The focus is on learner's perceptions with regards to enjoyment of doing the activity, learning English, usefulness after school and the understanding of reading Texts towards the ten reading activities selected by their teachers. Questionnaire consists of 40 item was administered to the whole population of Year 4 students and a semi-structured interview is conducted with four female teachers from the school. The findings seem to suggest that students prefer interactive types of reading activities more and all four variables should be taken into consideration when selecting and implementing reading activities in ESL classrooms.